Climate change and water insecurity in rural uMkhanyakude District Municipality: an assessment of coping strategies for rural South Africa - Hosea Olayiwola Patrick (IWA Publishing, 2021)
The vulnerability of Africa to climate change extremes and eventual impacts is extremely high due to the weak coping strategies prevalent in the continent. The peculiarity of South Africa to these vulnerabilities, especially for water security, is an issue of socioeconomic and policy issue. Based on the premises of human security, the study assesses the coping strategies of rural communities in South Africa, focusing on uMkhanyakude District Municipality, KwaZulu-Natal province, given the effects of climate change-induced water scarcity on the area. The study employed a multilayered descriptive mixed method triangulation approach. It focused specifically on the connection between water and climate change and the adopted everyday vertical and horizontal coping strategies. The findings revealed a strong correlation between the behavioral and traditional coping strategies in the study area, water depletion/scarcity, and climate change. It also showed that government institutions are reactionary in their response to climate change-induced impacts. The study, therefore, recommends a pre-resilience mechanism that makes institutions and individuals proactive rather than adopting a reactionary post-resilience strategy in response to the effects of climate change-induced water security. Highlights Water reuse seems to be the most common community strategy.; Community response is largely traditional and behavioral (such as water reuse, rainwater harvesting, and water rationing) largely due to the poor socioeconomic standing of most households within the area.; State institutions are reactionary rather than proactive in their intervention strategies.; Climate change is exacerbating water stress in the area.;